Using websites for learning basic grammar in the classroom / Rafidah Abd Karim and Zulkarnain Jamak - Abd Karim, Rafidah; Jamak, Zulkarnain (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Currently, language teachers and learners have various learning websites with interactive contents that offer certain advantages over conventional teaching instructions. Therefore, the aim of the study is to investigate the success of a technology and Internet-enriched teaching and learning environment in molding positive attitudes among students towards the website for grammar learning at a selected university in Malaysia. The survey design was utilized to carry out this study. 30 Diploma students had learnt basic grammar by using the websites and they were required to do the exercises from the websites. Results from the study indicated that students had positive attitudes toward using the websites as a grammar learning tool and viewed the learning environment as supportive of using the website for language learning. Thus, the university should introduce and promote the concepts of Web-based learning environments in classroom for language learning.